Effects of TiB2 particles and Ag on the activation energy of Ω phase in Al alloys. Issue 1 (March 2016) - Melotti, F; Hirst, T; Dustan, A; Griffiths, W D
Abstract: This work analyses the effects of TiB2 reinforcement particles and silver additions on the activation energy of the GP zones and the Ω phase in an aluminium matrix composite (AMC). Several additions of TiB2 and Ag were made to a 2xxx series alloy. Differential scanning calorimetry (DSC) was used to identify the temperature peaks and the Kissinger approach used to calculate activation energies. Results showed that the activation energy for the Ω phase was greatly reduced by the addition of both elements; however, the TiB2 particles were more effective. In addition, experimental results show that the lowest value of the activation energy, 68 kJmol -1, was not affected by the silver content. This value is lower than any value found in literature and suggests that the formation of the Ω phase is related to the pipe diffusion of Cu in Al.